The Signalling of Sustainability Reporting Award in Indonesia and Its Effects on Financial Performance and Firm Value - Prima Putri Citra Wardhani (Primrose Hall Publishing Group, 2019)
This research aims to test whether the Sustainability Reporting Award has an effect on a company’s financial performance and the firm value of nonfinancial public companies listed on the Indonesia Stock Exchange. This study uses panel data of 2,985 observations for the 8-year time period during 2010-2017. This research was conducted quantitatively with Ordinary Least Square (OLS) regression and uses robust standard errors to test the hypothesis. The statistical result of the test shows that the Sustainability Reporting Award has a positive and significant impact on both financial performance represented by ROA and firm value represented by Tobin’s Q.